Construction of an Attenuated Pasteurella Multocida B:2 by Mutation in the Gdha Gene - Othman, Siti Sarah (2007)
Pasteurella multocida 8:2 is a Gram negative bacteria that has been associated with haemorrhagic septicaemia in cattle and buffaloes in Asia. It has been known to produce endotoxin that leads to haemorrhages and oedema, causing deaths due to either asphyxiation and dyspnoea or septicaemia. Vaccination has been used to control the disease but with little success due to the low vaccination coverage. Therefore, an alternative live vaccine should be considered. In preparing an alternative live vaccine, an attenuated P. multocida 8:2 is created by manipulating one of the housekeeping genes of the bacteria. The selected housekeeping gene, the glutamate dehyrogenase (gdhA) gene, was successfully isolated via PCR from wild type P. multocida 8:2. The gene was then amplified using nested-PCR to determine its functional part. Both PCR products were cloned into plasmid pCR2.1, producing pSZ1 and pSZ2, respectively before being sequenced. The whole sequence of the gene is 1108 bp while the functional part of the gene was 652 bp. The functional part was 99.8% identical to the model sequence, the PM70, which is a model genome sequence of P. multocida serotype A. The pSZ 1 was subsequently digested with a unique restriction enzyme, Munl before the kanamycin cassette, isolated from plasmid pUC4K via PCR, was inserted at the centre of the housekeeping gene. The recombinant was named pSZ1K. After that, the gdhA gene that was disrupted by kanamycin cassette (GK) was isolated from the pSZ1K using restriction enzyme digestion, EcoRI. The suicide plasmid, pAKA19 was also digested with the same enzyme to achieve complimentary ligation sites. After ligation, the achieved recombinant plasmid was called pSZ19GK. All cloning products were transformed into Escherichia coli DH5a. Enroute for disruption of the gene in the host genome, both E. coli and P. multocida 8:2 were subjected to spontaneous mutation towards streptomycin. After conveying the pSZ19GK into P. multocida 8:2 via conjugation, the bacteria was incubated for five days to encourage allelic exchange to occur between disrupted gene and the host chromoso me. Subsequently, PCR of the bacteria genome proved that allelic exchange has occurred and the mutant was called P. multocida 8:2 (GK). In order to verify the characteristic of the non-pathogenic P. multocida 8:2 (GK) mutant, in vitro stability test and in vivo pathogenicity test were done. In in vitro stability test, 14 strains out of the 20 survived only up to 15 days of incubation. This proves that the mutants are unable to sustain life without glutamate supplement and therefore having a short life-span. From there, several strains were picked to be tested in vivo using mouse experimental model. Mice infected intraperitoneally or subcutaneously with different concentrations of the mutant survived throughout the 5-day study period. They were compared to the mice that were infected intraperitoneally or subcutaneously with different concentrations of the wild type organism. None of the mice infected with the mutant died but all mice infected with the wild type did not survived and were dead in less than 24 hours. P. multocida 8:2 were successfully isolated from organs of mice infected with both wild-type and mutant. This confirmed that the mutant, P. multocida 8:2 (GK) became attenuated by the disruption of the gdhA gene and has a good potential to be used as an alternative live vaccine for HS.